Boganmeldelser - Nils Jareborg; Anders Bratholm; Marcus Felson; Hartmut-Michael Weber; Keith Soothill; Roger Lane; James O. Finckenauer; Elin J. Waring; Cecilie E. Basberg (Nordisk Tidsskrift for Kriminalvidenskab)
Intet resumé